Effects of altered streamflow on macroinvertebrate taxonomic richness and composition in the Goulburn River, Australia - Banad, Sudeep; Wei, Yongping; Dhanya, C. T.; Johnstone, Ron (Frontiers in Environmental Science, 2023)
River systems have been stressed by the construction of dams and regulation structures which influence aquatic ecosystem integrity. Previous studies considered the general significance of regional streamflow regimes for aquatic communities, but they did not investigate the influence of specific components of flow regimes on aquatic ecosystems under the combined impact of regulation and extreme drought events, limiting our ability to design and implement precise environmental flow management strategies. This study aims to quantify the relationship between macroinvertebrate biotic indices and ecologically important streamflow characteristics derived from five natural flow regime components by investigating the spatiotemporal variation in the macroinvertebrate assemblage in regulated and unregulated reaches and identifying specific flow indices that have a direct impact on macroinvertebrates in the Goulburn basin in Victoria, Australia during the Millennium Drought period. The relationship between dominant flow metrics and macroinvertebrates indices was investigated using boosted regression trees (BRT). The results revealed a significant difference in hydrological variability between regulated and unregulated reaches. The regulated reaches demonstrated reduced hydrological variability during low flow periods, and rapid increase in discharge during high flow periods when compared to unregulated reach. Unregulated reach had 38% more taxa richness than regulated reach impacted by hydropeaking. 8 indicator taxa were identified in the unregulated reach, and they exhibited a higher Stream Invertebrate Grade Number Average Level (SIGNAL 2) score, indicating that they were highly sensitive species. The maximum flow in June was the most important flow parameter that influences the macroinvertebrate indices as per the BRT model. Better management of environmental flows will benefit from identifying which aspects of the natural flow regime impact stream ecosystems and predicting the consequences of altered flow regimes on aquatic ecosystems.